Experimental validation of the thermodynamic theory for predicting the strength of 6061 Al alloy with complex loadings. (January 2023) - Chen, Bin; Chen, Jiapeng; Li, Runxia; Wang, Biao
Highlights: A general thermodynamic theory for predicting the strength of materials was developed. The plastic dissipation energy density function of 6061 Al alloy was determined by uniaxial and biaxial tensile tests. Experimental validation of the predicted failure strength in stress and strain space under different loading conditions was carried out. Abstract: The safety and reliability of engineering structures face severe challenges all the time. Determining how to accurately predict the strength of material structures is a major issue for academia and industry. Recently, a general thermodynamic theory was proposed by Wang [Eng Fract Mech., 2021, 254: 107936] to predict the failure properties of material structures beyond classical strength criteria. In this study, the thermodynamics-based method is applied to predict the strength of 6061 Al alloy with complex loadings, accompanied by experimental validation. The plastic dissipation energy density function is established and its expansion coefficients are determined by uniaxial and equi-biaxial tensile tests. Then, the predicted failure strength of the 6061 Al alloy in stress space and strain space is obtained, which matches well with the experimental results. Moreover, a comparison between our prediction and the results of two classical strength theories, i.e., the maximum shear stress and maximum distortion energy theories, was performed. In summary, this study verifies the accuracy and reliability of the thermodynamic theory for predicting the strength of material structures with complex loadings, which lays the foundation for the engineering applications of the non-empirical thermodynamic method.